SOME POSSIBILITIES IN COUNTERINSURGENCY OPERATIONS - Heitman, H.R (Scientia Militaria - South African Journal of Military Studies, 2012)
It is often held that there can be no ’military’ solution to an insurgency. As a general rule this is probably true but it is rather dependant on what is understood by terms ’insurgency’, ’solution’ and ’military’. It is therefore probably worthwhi Ie looking at these terms more closely. For the purposes of this paper these terms will be used in the following sense: